Description of the Sorogan Method in learning the Qur'an at the Al-Irfan IslamBiBc Boarding School in Bukittinggi - Hendra H; Hakekat Rabbani Ikhsan; Afrizal A; M. Maulana Ibrahim; Muhammad Nurhabib; Zulfani Sesmiarni (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to provide a comprehensive overview of the application of the sorogan method in the Qur'an learning process at the Al-Irfan Islamic Boarding School in Bukittinggi. As a traditional method that has long been a hallmark of Islamic boarding schools, sorogan is still practiced because it is considered capable of improving pronunciation accuracy, understanding tajwid, and building closeness between teachers and students. This study used a descriptive qualitative approach with data collection techniques through direct observation, in-depth interviews, and document review. While data analysis was conducted using the interactive model of Miles, Huberman, and Saldana. The research findings indicate that sorogan functions as an important mechanism in fostering students' personal reading skills, strengthening character formation, and creating a more humanistic learning atmosphere. Regular implementation, group division according to ability level, and individual reading evaluations contribute to improving student competency. However, the study also identified several obstacles, particularly related to the motivation and discipline of some students. Overall, the research results confirm that sorogan remains relevant in contemporary Islamic boarding school education and has the potential to be improved through strengthening motivation, more effective classroom management, and more targeted mentoring.